If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12(4x + 6) + x = -26 Reorder the terms: 12(6 + 4x) + x = -26 (6 * 12 + 4x * 12) + x = -26 (72 + 48x) + x = -26 Combine like terms: 48x + x = 49x 72 + 49x = -26 Solving 72 + 49x = -26 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-72' to each side of the equation. 72 + -72 + 49x = -26 + -72 Combine like terms: 72 + -72 = 0 0 + 49x = -26 + -72 49x = -26 + -72 Combine like terms: -26 + -72 = -98 49x = -98 Divide each side by '49'. x = -2 Simplifying x = -2
| (3x+20)=(5x+50) | | 2x+1=2-1 | | 16p-4=8(2p-3) | | 3(2-x)=3-(3-x) | | 3/8=a+4/5 | | -5x+24=x | | 6x=-43 | | 2-6y+3=3y+14-6y | | -1.2=-4.79+n | | 15x+22+2=180 | | 486+.03a=490+.02a | | 12(m+3)+5m=70 | | -3=x+(-1) | | 15x+22=180 | | 8y+14=3y+49 | | -14=q-18 | | 67=7-3(5x-10) | | 6(x+7)x=9 | | B+(-14)=6 | | 14-9x=82-37x | | 42=2(2x-7)+2(x+4) | | 5(2x+3)=-(x-4) | | 3x^4-16x^3+18x^2=0 | | 3.8x+3.4=14.8 | | (r^4)+(r^3)-(7r^2)-r+6=0 | | 2x+70=7x+30 | | 3(x+2)=7x | | -3(-4x-4)=-4 | | 56-3x=8x | | (6x+4)=(8x-8) | | 3/8=27 | | 3.1416*8= |